Women Reading for Education, Affinity & Development (WREAD): An Evaluation of a Semi-Structured Reading Discussion Group For African American Female Adult Literacy Students - Jaye Jones (Adult Education Research Conference, 2012)
Women Reading for Education, Affinity & Development (WREAD), a reading discussion group geared toward African American female adult literacy students with self-defined histories of trauma, was an outgrowth of research identifying links between trauma, women‘s struggles with literacy, and the need to be conscious of emotional health concerns in adult education classrooms. The structure of the group was grounded in theories of relational-cultural theory (RCT), critical pedagogy and black feminist theory; and combined thematically arranged literary materials (i.e., poetry, texts and films), critical group discussion and cultural activities. The use of a mixed-method, feminist qualitative analytic approach illustrated how educational interventions like WREAD can lead to literacy gains, improved psychological self-awareness and positive group connections among women with difficult socioemotional histories.